THE CORRELATION BETWEEN A FAMILY SITUATION WITH DRUGS RELAPSE BEHAVIOR TO RESIDENT - Deny Kurniawan; Ratna Yuliawati; Ari Hamdani (Promotif : Jurnal Kesehatan Masyarakat, 2017)
The rehabilitation centers BNN Tanah Merah incerease in rehabilitated drug users since 2013 from 5 people to 68 people in 2016. This study is intend to research is to determine correlation between a family situation with drugs relapse behavior to resident in Rehabilitation centers BNN Tanah Merah Samarinda. This research using Cross Sectional research design and the sampling technique used probability sampling with simple random sampling type.This research using a Chi Square statistic test. Based on the result, a good family situation respondents but still experience the relapse are 18.9% and a bad family situation respondents and still experience the relapse are 19,0%. Statistically obtained p-value 1.00 (p<0.05). it can be concluded that there is no correlation between a Family Situation with drugs relapse behavior to resident at Rehabilitation centers BNN Tanah Merah Samarinda.Keywords : Family situation, Relapse, Drugs, Resident.